Proceedings of the Seventh International Workshop on Natural Language Generation - INLG '94 1994
DOI: 10.3115/1641417.1641425
|View full text |Cite
|
Sign up to set email alerts
|

Expressing procedural relationships in multilingual instructions

Abstract: In this paper we discuss a study of the expression of procedural relations in multilingual user instructions~ in particular the relations of Gene,ution and Enablement. These procedural relations are defined in terms of a plan representation model, and applied in a corpus study of English, French, and Portuguese instructions. The results of our analysis indicate specific guidelines for the tactical realisation of expressions of these relations in multilingual instructional text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 4 publications
0
21
0
6
Order By: Relevance
“…Examples of varying rhetorical structures across translation equivalents found in work on the drafter system (Delin et al, 1994) viewpoint, this corresponds to rejecting the Chomskyan idea of a Universal Grammar, replacing it with the notion of a Typological Universal Grammar where it can be assumed both that languages differ and that shared characteristics will nevertheless be observed. Thus, although the German, French and English rhetorical organizations proposed by Delin et al (1994) are different, they are all drawn from a collectively shared and multilingually valid statement of rhetorical structure. The question remains, therefore, to what extent such system-level congruences can be maintained even though, as we saw in §1 with our example CADsoftware manual headings, individual texts and languages may make very different use of those systems during the generation of particular texts.…”
Section: The Multilingual Natural Language Generation Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Examples of varying rhetorical structures across translation equivalents found in work on the drafter system (Delin et al, 1994) viewpoint, this corresponds to rejecting the Chomskyan idea of a Universal Grammar, replacing it with the notion of a Typological Universal Grammar where it can be assumed both that languages differ and that shared characteristics will nevertheless be observed. Thus, although the German, French and English rhetorical organizations proposed by Delin et al (1994) are different, they are all drawn from a collectively shared and multilingually valid statement of rhetorical structure. The question remains, therefore, to what extent such system-level congruences can be maintained even though, as we saw in §1 with our example CADsoftware manual headings, individual texts and languages may make very different use of those systems during the generation of particular texts.…”
Section: The Multilingual Natural Language Generation Perspectivementioning
confidence: 99%
“…However, based on corpus work on instructional texts in Portuguese, Italian, English, French and German preparatory to designing the resources for the drafter-I multilingual text generation system, examples were found which even appeared to require different rhetorical structures. One such set of contrasting examples discussed in Delin et al (1994) is shown in Figure 1. The distinct rhetorical structures posited as text-level descriptions of the three 'translations' are quite different in their communicative force.…”
Section: The Multilingual Natural Language Generation Perspectivementioning
confidence: 99%
“…This approach has occasionally been taken, as in Kantrowitz and Bates (1992) and Danlos (1987) 4 and, at least implicitly, in Paris and Scott (1994) and Delin et al (1994); however, under this approach, all of the flexibility and simplicity of modular design is lost.…”
Section: Facing the Dilemmamentioning
confidence: 99%
“…An earlier attempt for language generation is e.g. (Delin 1994). Semantic tags are either close to thematic roles (instrument, location, etc.)…”
Section: The Question-answering Process Annotationmentioning
confidence: 99%